1994
DOI: 10.1001/jama.1994.03520060049031
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of HIV and Risk Behaviors Among Young Homosexual and Bisexual Men

Abstract: The prevalence of HIV infection is high among this young population of homosexual and bisexual men, particularly among young African-American men. The high rates of HIV-related risk behaviors suggest a considerable risk for HIV transmission in this population. Prevention programs and health services need to be tailored to address the needs of a new generation of homosexual and bisexual men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(49 citation statements)
references
References 11 publications
6
42
0
1
Order By: Relevance
“…Bingham et al (2003) review this issue and find that there are studies finding higher, similar, and lower levels of unprotected anal sex by African American MSM as compared to White MSM (Easterbrook et al, 1993;Heckman, Kelly, Bogart, Kalichman, & Rompa, 1999;Lemp et al, 1994;, 1990b, 1993Rotheram-Borus, Reid, & Rosario, 1994;Ruiz, Facer, & Sun, 1998). In the recent young men's studies cited above (CDC 2001(CDC , 2002(CDC , 2003, rates of risky sexual behavior by African American MSM as compared to their White counterparts were not higher despite the higher rates of seroprevalence (Bingham, Harawa, Ford, & Gatson, 1999).…”
Section: Incidence and Prevalence Of Hiv Infections In African Americmentioning
confidence: 99%
“…Bingham et al (2003) review this issue and find that there are studies finding higher, similar, and lower levels of unprotected anal sex by African American MSM as compared to White MSM (Easterbrook et al, 1993;Heckman, Kelly, Bogart, Kalichman, & Rompa, 1999;Lemp et al, 1994;, 1990b, 1993Rotheram-Borus, Reid, & Rosario, 1994;Ruiz, Facer, & Sun, 1998). In the recent young men's studies cited above (CDC 2001(CDC , 2002(CDC , 2003, rates of risky sexual behavior by African American MSM as compared to their White counterparts were not higher despite the higher rates of seroprevalence (Bingham, Harawa, Ford, & Gatson, 1999).…”
Section: Incidence and Prevalence Of Hiv Infections In African Americmentioning
confidence: 99%
“…It is quite simple to identify the relationship between the exposure to risk and an adverse outcome especially in infectious diseases. [1,4] However, in chronic diseases such as cancer, metabolic, and heart diseases, it is less clear and even more ambiguous and complex when such illnesses result to coma. This is because, irrespective of cause, coma rarely lasts more than 2-4 weeks without an outcome, which can be either of the following: recovery with no disability, recovery with various degrees of disability, vegetative state, or death.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Through the use of case-control and cohort studies, (as in the present study), risk and prognostic factors can be determined, which will allow screening programs and health promotion strategies aimed at changing risk behaviors to be established. [4] According to the literature, socio-economic factors may contribute more to the outcome of non-traumatic coma than has previously been recognized. [7] These factors include socio-economic variables in the individual patients, their families, and the hospitals or health institutions.…”
Section: Introductionmentioning
confidence: 99%
“…Fourteen studies examined rates of UAI, and all found that API MSM engaged in similar rates of UAI compared to White MSM or race/ethnicity was not associated with UAI [7,10,13,[15][16][17][18][19][20][21][22][23][24][25]. The San Francisco/Berkeley Young Men's Study found that 27% of API young men who have sex with men (YMSM) reported UAI in the past 6 months compared to 28% of White YMSM [10].…”
Section: Resultsmentioning
confidence: 99%
“…Existing epidemiological data shows that API MSM engage in high levels of HIV-related risk behaviors including unprotected anal intercourse and substance use [3][4][5]. Yet, HIV prevalence and incidence rates have been much lower among API MSM than among MSM of other races/ethnicities, especially other racial/ethnic minority MSM [6][7][8][9][10][11]. For example, the Urban Men's Health Study found that HIV prevalence was 16% among API MSM in San Francisco compared to 25% among Whites, 38% among Blacks, and 31% among Latinos [6].…”
Section: Introductionmentioning
confidence: 99%